EFEKTIVITAS EKSTRAK BUNGA KECOMBRANG ( Etlingera elatior ) SEBAGAI REPELLENT NYAMUK Aedes aegypti - DEWI MUSTIKA RANI GURNING; irnawati marsaulina; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Aedes aegypti often cause health problems, especially dengue disease. To control its population were used insecticides. However, the use of chemical insecticides cause many problems. As we know,  Aedes aegypty is the main vector of dengue disease. Today there is no effective way to overcome the dengue disease, because until today have not found the drugs effective anti-dengue virus and a vaccine that can protect themselves from dengue virus infection. One way to combating dengue vector control is by using synthetic insecticides. There are two major categories of insecticides which is often used as a household insecticide, and they are the insecticide which is used to kill insects and insecticides which is  function to repel the insects. Therefore, it is necessary insecticides safer alternatives for the environment, one of them is by using the kecombrang flower extracts  (Etlingera elatior). The purpose of this study was to determine the effectiveness of kecombrang flower extract as reppelent of Aedes aegypti mosquitoes. This study was a quasi-experimental study with a completely randomized design (CRD). Kecombrang flower extract concentration used was 0% (control), 1%, 2%, 3%, 4% and 5%. From the research, the best concentration is 5% the number of mosquitoes which was away  is  19. One Way ANOVA test 30 menute observation, it is known that the number of mosquitoes which away, there is differences in effectiveness significantly between kecombrang flower extracts as reppelent of Aedes aegypti mosquitoes with value of p (0.000) < 0.05, 60 menute observation, there is no differences in effectiveness significantly between kecombrang flower extracts as reppelent of Aedes aegypti mosquitoes with value of p (0.542) > 0.05, Based on this research it can be concluded that the kecombrang flower extract was effective as an  reppelent and killed Aedes aegypti mosquito effectively. Keywords: flower extract kecombrang (Etlingera elatior), reppelent, Aedes aegypti